Molecular investigation of occult hepatitis B virus infection in a reference center in Northern Brazil - Araújo,Suellen dos Reis (2022)
ABSTRACT The goal of this study was to investigate the prevalence of occult HBV infection in a reference center for the Northern Brazil from 2005 to 2015 and to identify mutations associated with occult hepatitis B. Molecular analysis was performed on 110 serum samples in which anti-HBc was the only positive serological marker. Regions of the HBV genome were amplified by polymerase chain reaction to detect HBV DNA. A prevalence of 4.1% (793/18,889) for anti-HBc alone was identified. Molecular analysis revealed a prevalence of occult HBV infection of 0.04%. HBV DNA detected were identified in individuals who underwent hemodialysis, infected with the hepatitis C virus and from area of high endemicity for HBV. Direct DNA nucleotide sequencing and phylogenetic analysis identified that genotypes A and D and mutations E164D, I195M, P217L and P120S were associated with occult HBV infection in the S gene. This study contributed with epidemiological and molecular information on Northern Brazil samples with a suggestive profile of occult HBV infection in addition to reinforcing the importanceof molecular diagnosis in this type of infection.